Organization development in healthcare : a guide for leaders - Wolf, Jason; Hanson, Heather; Moir, Mark (Contemporary trends in organization development and change., 2011)
In a world saturated with the "how tos" of OD, there is a void of evidence-based resources for both organizational leaders and OD scholar-practitioners to use as a guide while navigating the complex and chaotic environment of healthcare. This handbook has been created to fill this space and provide a resource for this vital audience at a time of great change and greater potential in the healthcare arena. The handbook will focus on the critical nature of OD in healthcare and how it applies in this unique environment; examining its broad use from hospitals to corporate offices and from small systems to multinational corporations. The book will provide research-based, practical processes and methods, while sharing compelling cases of how the compassion and care associated with healthcare is wound tightly with the OD work it encompasses.The handbook will also offer a comprehensive look at the role OD plays in the critical issues and significant changes facing healthcare today. The handbook overall is a small part history and a small part predictions surrounding very practical and applicable uses of OD In healthcare. Through the sharing of engagement processes, revealing outcomes and connecting each concept to a living case of how OD has impacted the healthcare field, this handbook provides a unique resource for OD and HR professionals, healthcare executives, MHA students and the academic community.